IMPLEMENTASI HUKUM PERUMAHAN SEBAGAI USAHA PERCEPATAN PENGADAAN RUMAH BAGI MASYARAKAT YANG BERPENGHASILAN RENDAH (MBR) - Sudiman Sihotang (JURNAL HUKUM DE'RECHTSSTAAT, 2016)
In the preamble of the two basic considerations Act No. 1 of 2011 on  Housing  and  Region Settlements (Act PKP "That the state is  responsible for protecting  all Indonesian  citizens through the  implementation of housing and residential areas so  that people  can  live and  occupy decent housing and affordable in the housing healthy, safe, harmonious, and sustainable in all regions of Indonesia. "Although the regulations with regard to the procurement of low-income housing has  been  a lot made, but the fact still occur backlog (number gap between the need and availability of home) as contained in the  Strategic Plan of   the Ministry of  Public Works and public housing in 2015-2019 which states that until 2014, the remaining backlog of as many as 11.4 million homes. this reflects the need to optimize housing law to accelerate the supply of homes for low income people (MBR). by using the methodology and theories from the academic side, the present study was designed to find out why the housing law has  not  been effective in an effort to facilitate  access to home ownership for MBR and also to know how to optimize housing law to facilitate  access  to home ownership for MBR. Therefore the targeted outcomes of this study apart from a Dissertation (draft dissertation) approved supervisor, scientific publications in journals of international repute and enrichment of teaching materials on the subject property law in Indonesia that is taught at the Faculty of the University of Djuanda Bogor. This study also we target to become an academic paper for the improvement of relevant legislation Property in Indonesia